Sodium battery positive electrode material as well as preparation method and application thereof
By introducing bismuth elements into the core of vanadium phosphate and using a double-clad structure of porous carbon and B2O3, the problem of poor rate performance and cycle performance of vanadium phosphate material at high current density is solved, and the excellent performance and long cycle life of sodium batteries at high current density is achieved.
Patent Information
- Application Number
- CN202510172597.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing vanadium sodium phosphate materials have poor rate performance and cycle performance at high current density, which limits their practical application in sodium ion batteries.
Doping modification is performed by introducing bismuth elements into the core of sodium vanadium phosphate, and a double-clad layer structure of porous carbon and B2O3 is used to form a sodium electropositive electrode material doped with bismuth vanadium phosphate @ porous carbon @B2O3.
It improves the rate performance and cycle performance of sodium batteries at high current density, extends the cycle life of the battery, and reduces the polarization phenomenon of the battery.
Smart Images

Figure BDA0005274478860000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Compared with the scarcity and uneven distribution of lithium resources, sodium resources are abundant and evenly distributed, which makes sodium-ion batteries have advantages in raw material cost and sufficient supply, which can make up for the shortcomings of lithium batteries. The positive electrode materials of sodium-ion batteries are mainly divided into transition metal oxides (layered oxides and three-dimensional tunnel oxides), polyanionic compounds, and Prussian blue (white) compounds. Among them, polyanionic compounds have the advantages of rich variety, structural stability and high safety. However, the electrical conductivity of polyanionic compounds is generally poor, and they have strong water absorption, which affects the electrochemical performance. Therefore, they have always attracted the attention of researchers.
[0003] Polyanionic compounds are mainly divided into phosphates, sulfates and other types. Among them, sodium vanadium phosphate (Na3V2(PO4)3, NVP) as a representative polyanion positive electrode material has shown unique advantages and broad application prospects in the field of sodium ion batteries. First, Na3V2(PO4)3 has a stable three-dimensional skeleton structure, which allows sodium ions to be quickly transported in the material; secondly, through the redox reaction of vanadium, the discharge capacity of Na3V2(PO4)3 can reach 117.6mAh / g, showing a high theoretical capacity; in addition, Na3V2(PO4)3 has excellent structural stability and thermal stability, which is conducive to the long cycle life of the battery. Although Na3V2(PO4)3 has many advantages mentioned above, it is precisely because of the particularity of its structure and the insulating properties of the anion that it has poor conductivity and slow electron migration rate, which reduces the charge and discharge performance of the battery at high current density, resulting in low capacity, poor rate performance and cycle performance of the battery at high current density, thus limiting its practical application. Summary of the invention
[0004] The purpose of the present invention is to provide a sodium positive electrode material, a preparation method and an application thereof, in view of the fact that the sodium vanadium phosphate material prepared by the prior art still has the disadvantages of poor rate performance and cycle performance under high current density.
[0005] In a first aspect, the present invention provides a sodium positive electrode material.
[0006] Specifically, the sodium positive electrode material includes a bismuth-doped sodium vanadium phosphate core and a first coating layer and a second coating layer sequentially coated on the surface of the bismuth-doped sodium vanadium phosphate core from the inside to the outside; the first coating layer is porous carbon, and the second coating layer is B2O3.
[0007] In a preferred embodiment, the bismuth content in the bismuth-doped sodium vanadium phosphate core is 0.3-0.8 wt %.
[0008] In a preferred embodiment, the content of porous carbon in the sodium positive electrode material is 0.5-1.5 wt %.
[0009] In a preferred embodiment, the content of B2O3 in the sodium positive electrode material is 0.5-1 wt%.
[0010] In a second aspect, the present invention provides a method for preparing a sodium positive electrode material. The preparation method comprises the following steps: S1. After a sodium source, a vanadium source, a bismuth source, a phosphorus source, citric acid and water are subjected to a first mixing treatment, the obtained first intermediate product is subjected to a pore-forming treatment in the presence of an activator, and the obtained second intermediate product is subjected to a first calcination treatment to obtain a porous carbon @ bismuth-doped sodium vanadium phosphate material; S2. After a porous carbon @ bismuth-doped sodium vanadium phosphate material is subjected to a second mixing treatment with B2O3, the obtained third intermediate product is subjected to a second calcination treatment to obtain a sodium positive electrode material.
[0011] In a preferred embodiment, the molar ratio of the vanadium source to the sodium source, bismuth source, phosphorus source and citric acid is 1:(1-3):(0.015-0.05):(1.5-3):(1.5-3).
[0012] In a preferred embodiment, the molar ratio of the activator to the vanadium source is (0.02-0.05):1.
[0013] In a preferred embodiment, the amount of B2O3 used is 0.5-1 wt% of the porous carbon@bismuth-doped sodium vanadium phosphate material.
[0014] In a preferred embodiment, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0015] In a preferred embodiment, the vanadium source is selected from ammonium metavanadate and / or vanadium pentoxide.
[0016] In a preferred embodiment, the bismuth source is selected from bismuth nitrate and / or bismuth acetate.
[0017] In a preferred embodiment, the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium phosphate.
[0018] In a preferred embodiment, the activator is selected from at least one of sodium bicarbonate, potassium bicarbonate, potassium hydroxide and sodium hydroxide.
[0019] In a preferred embodiment, the conditions of the first mixing treatment include: a temperature of 70 to 90° C. and a time of 1 to 3 hours.
[0020] In a preferred embodiment, the pore-forming treatment conditions include: a temperature of 70 to 90° C. and a time of 7 to 8 hours.
[0021] In a preferred embodiment, the second mixing process is a ball milling process.
[0022] In a preferred embodiment, the second mixing treatment is performed for 2 to 4 hours.
[0023] In a preferred embodiment, the conditions of the first calcination treatment include: a temperature of 700-800° C., a time of 6-8 hours, and an inert gas atmosphere.
[0024] In a preferred embodiment, the conditions of the second calcination treatment include: a temperature of 800-900° C. and a time of 8-15 hours.
[0025] In a third aspect, the present invention also provides a sodium positive electrode material prepared by the above method.
[0026] In a fourth aspect, the present invention further provides a sodium battery positive electrode sheet, wherein the sodium battery positive electrode sheet comprises the above-mentioned sodium battery positive electrode material.
[0027] In a fifth aspect, the present invention further provides a sodium battery, which comprises the above-mentioned sodium positive electrode material.
[0028] The key to the present invention is to design and synthesize a sodium positive electrode material with a specific core-shell structure, which is modified by introducing bismuth into the sodium vanadium phosphate core for doping, and at the same time introducing porous carbon and B2O3 to form a double coating structure for the bismuth-doped sodium vanadium phosphate core. The sodium positive electrode material thus obtained has good electrochemical properties and structural stability, and can promote the transmission of ions and electrons, thereby improving the rate performance and cycle performance of the sodium battery at high current density. It is speculated that the reason may be due to: the introduction of bismuth into the sodium vanadium phosphate core is beneficial to broaden the ion channel, improve the efficiency of sodium ion insertion and extraction, so that the sodium battery can efficiently transmit ions during the charge and discharge process, which is beneficial to improve the rate performance of the battery. On the other hand, it can enhance the structural stability of the sodium positive electrode material, reduce the structural damage caused by volume changes and other problems during the charge and discharge process of the sodium battery, thereby extending the cycle performance and service life of the sodium battery. At the same time, Bi 3+It can react with HF produced by the battery side reaction to generate relatively stable bismuth fluoride, effectively reducing the corrosion of HF to the battery, which is beneficial to prolonging the cycle performance and service life of the sodium battery; the rich pore structure of the porous carbon can provide more active sites, promote the rapid transmission of electrons and ions, and the porous carbon structure is stable, which is beneficial to improve the cycle stability and service life of the sodium battery; the B2O3 coating layer can further promote the migration and diffusion of sodium ions, improve the overall conductivity of the positive electrode material, reduce the internal resistance of the battery, thereby improving the electrochemical performance of the battery, and the B2O3 coating layer can also reduce the interface reaction between the positive electrode material and the electrolyte, protect the positive electrode active material from the erosion of the electrolyte, reduce the polarization phenomenon of the battery, and improve the battery cycle performance. In summary, the sodium positive electrode material provided by the present invention improves the structural stability and overall electrochemical performance of the positive electrode material through the synergistic cooperation between bismuth doping, porous carbon and B2O3 double coating layer structure, promotes the rapid transmission of ions and electrons during charging and discharging, thereby improving the rate performance and cycle performance of the sodium battery at high current density, and has good promotion and application value. DETAILED DESCRIPTION
[0029] The sodium positive electrode material provided by the present invention comprises a bismuth-doped sodium vanadium phosphate core and a first coating layer and a second coating layer sequentially coated on the surface of the bismuth-doped sodium vanadium phosphate core from the inside to the outside; the first coating layer is porous carbon, and the second coating layer is B2O3.
[0030] In the present invention, the content of bismuth in the bismuth-doped sodium vanadium phosphate core is preferably 0.3-0.8wt%, such as 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or any value therebetween, which is more conducive to improving the efficiency of sodium ion insertion and extraction and improving structural stability, thereby further optimizing the rate performance and cycle performance of the positive electrode material. The content of porous carbon in the sodium positive electrode material is preferably 0.5-1.5wt%, such as 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt% or any value therebetween, which is more conducive to reducing the internal resistance of the material and promoting the transmission of electrons and ions during charging and discharging. The content of B2O3 in the sodium positive electrode material is preferably 0.5-1wt%, such as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value therebetween, which is more conducive to reducing the barriers to sodium ion migration and diffusion on the basis of achieving uniform coating of the bismuth-doped sodium vanadium phosphate core, thereby further optimizing the electrochemical performance of the battery.
[0031] The method for preparing the sodium positive electrode material provided by the present invention comprises the following steps:
[0032] S1. After a sodium source, a vanadium source, a bismuth source, a phosphorus source, citric acid and water are subjected to a first mixing treatment, the obtained first intermediate product is subjected to a pore-forming treatment in the presence of an activator, and the obtained second intermediate product is subjected to a first calcination treatment to obtain a porous carbon @ bismuth-doped sodium vanadium phosphate material;
[0033] S2. After the porous carbon@bismuth-doped sodium vanadium phosphate material is subjected to a second mixing treatment with B2O3, the obtained third intermediate product is subjected to a second calcination treatment to obtain a sodium positive electrode material.
[0034] In the present invention, the molar ratio of the vanadium source to the sodium source, bismuth source, phosphorus source and citric acid is preferably 1:(1-3):(0.015-0.05):(1.5-3):(1.5-3). Taking the amount of the vanadium source as 1 mol, the amount of the sodium source is preferably 1-3 mol, such as 1 mol, 1.5 mol, 2 mol, 2.2 mol, 2.5 mol, 2.8 mol, 3 mol or any value therebetween. Taking the amount of the vanadium source as 1 mol, the amount of the bismuth source is preferably 0.015-0.05 mol, such as 0.015 mol, 0.02 mol, 0.025 mol, 0.03 mol, 0.035 mol, 0.04 mol, 0.045 mol, 0.05 mol or any value therebetween. Based on the amount of the vanadium source as 1 mol, the amount of the phosphorus source is preferably 1.5 to 3 mol, such as 1.5 mol, 2 mol, 2.2 mol, 2.5 mol, 2.8 mol, 3 mol or any value therebetween. Based on the amount of the vanadium source as 1 mol, the amount of the citric acid is preferably 1.5 to 3 mol, such as 1.5 mol, 2 mol, 2.2 mol, 2.5 mol, 2.8 mol, 3 mol or any value therebetween. In the first mixing treatment, the amount of water is not specifically limited and can be determined according to actual conditions, as long as the added sodium source, vanadium source, bismuth source, phosphorus source and citric acid can be fully mixed and uniformly mixed.
[0035] In the present invention, the molar ratio of the activator to the vanadium source is preferably (0.02-0.05): 1. Based on 1 mol of the vanadium source, the amount of the activator is preferably 0.02-0.05 mol, such as 0.02 mol, 0.03 mol, 0.04 mol, 0.05 mol or any value therebetween.
[0036] In the present invention, the amount of B2O3 is preferably 0.5-1wt% of the porous carbon@bismuth-doped sodium vanadium phosphate material, such as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value therebetween.
[0037] In the present invention, specific examples of the sodium source include, but are not limited to, at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0038] In the present invention, the vanadium source is preferably selected from ammonium metavanadate and / or vanadium pentoxide.
[0039] In the present invention, the bismuth source is preferably selected from bismuth nitrate and / or bismuth acetate.
[0040] In the present invention, specific examples of the phosphorus source include, but are not limited to, at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium phosphate.
[0041] In the present invention, specific examples of the activator include, but are not limited to, at least one of sodium bicarbonate, potassium bicarbonate, potassium hydroxide, and sodium hydroxide.
[0042] In the present invention, the first mixing treatment is preferably a mechanical stirring treatment. The conditions of the first mixing treatment preferably include: a temperature of 70 to 90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; and a time of 1 to 3 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any value therebetween.
[0043] In the present invention, the conditions for the pore-forming treatment preferably include: a temperature of 70 to 90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; and a time of 7 to 8h, such as 7h, 7.2h, 7.5h, 7.8h, 8h or any value therebetween.
[0044] Furthermore, in the first mixing treatment, the mixing order of the sodium source, vanadium source, bismuth source, phosphorus source, citric acid and water is not specifically limited. The sodium source, vanadium source, bismuth source, phosphorus source, citric acid and water may be added and mixed at the same time, or several of the raw material components may be mixed first and then the remaining raw material components may be mixed. In a specific embodiment, the steps of the first mixing treatment and the second mixing treatment are preferably as follows: the vanadium source, citric acid and water are mixed evenly to obtain solution A, the sodium source, bismuth source, phosphorus source and water are mixed evenly to obtain solution B, solution A and solution B are mixed and stirred in a water bath at 70 to 90° C. for 1 to 3 hours, an activator is added when the color of the solution is stable in blue, and stirring is continued in a water bath at 70 to 90° C. for 7 to 8 hours to form a gel, and then a second intermediate product is obtained after vacuum drying. The vacuum drying conditions preferably include: a temperature of 110-130°C, such as 110°C, 115°C, 120°C, 125°C, 130°C or any value therebetween; and a time of 12-15h, such as 12h, 13h, 14h, 15h or any value therebetween.
[0045] In the present invention, the second mixing treatment is preferably ball milling. The time of the second mixing treatment is 2 to 4 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or any value therebetween.
[0046] In the present invention, the conditions of the first calcination treatment preferably include: a temperature of 700-800°C, such as 700°C, 720°C, 750°C, 780°C, 800°C or any value therebetween; a time of 6-8h, such as 6h, 6.5h, 7h, 7.5h, 8h or any value therebetween; and an inert gas atmosphere, wherein the inert gas is preferably at least one of nitrogen, argon and xenon.
[0047] In the present invention, the conditions of the second calcination treatment preferably include: a temperature of 800 to 900°C, such as 800°C, 820°C, 850°C, 880°C, 900°C or any value therebetween; a time of 8 to 15 hours, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any value therebetween. The second calcination treatment is preferably carried out under an inert gas atmosphere. The inert gas can be conventionally selected and can be nitrogen, helium or argon.
[0048] The present invention also provides application of the sodium positive electrode material in a sodium battery.
[0049] The present invention provides a sodium battery positive electrode sheet, which comprises the sodium battery positive electrode material.
[0050] The present invention provides a sodium battery, which comprises the above-mentioned sodium battery positive electrode material.
[0051] In addition, the terms "first", "second" and "third" are only for the purpose of convenience of description and should not be understood as special limitations on the type or quantity of technical features.
[0052] The present invention will be described in detail below through specific embodiments.
[0053] Example 1 Preparation of sodium positive electrode material
[0054] S1. Preparation of porous carbon-coated bismuth-doped sodium vanadium phosphate material: ammonium metavanadate, sodium acetate, bismuth nitrate, ammonium dihydrogen phosphate, and citric acid are weighed in a molar ratio of 1:1.5:0.015:1.5:1.5, the vanadium source and citric acid are dissolved in deionized water to obtain solution A, the sodium source, bismuth source, and phosphorus source are dissolved in deionized water to obtain solution B, solution A and solution B are mixed and placed in a water bath at 80°C for constant heating and stirring for 1 hour to stabilize the color of the solution at blue, and then sodium bicarbonate is added (sodium bicarbonate is 2% of the amount of the added vanadium source), and stirring is continued for 7 hours to form a gel, and then dried in a vacuum oven at 120°C for 12 hours and ground into powder, and then placed in a nitrogen atmosphere and sintered at 700°C for 8 hours to obtain porous carbon@bismuth-doped sodium vanadium phosphate material.
[0055] S2. Preparation of B2O3 coating layer: The porous carbon-coated bismuth-doped sodium vanadium phosphate material obtained in step S1 is ball-milled with B2O3 for 3 hours, wherein the amount of B2O3 used is 0.6wt% of the porous carbon-coated bismuth-doped sodium vanadium phosphate material, and then placed in a nitrogen atmosphere, sintered at 800°C for 12 hours, and cooled to room temperature to obtain B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (the bismuth content is 0.33wt%, the porous carbon content is 1.3wt%, and the B2O3 content is 0.53wt%).
[0056] Example 2 Preparation of sodium positive electrode material
[0057] S1. Preparation of porous carbon-coated bismuth-doped sodium vanadium phosphate material: Vanadium pentoxide, sodium acetate, bismuth nitrate, ammonium dihydrogen phosphate, and citric acid are weighed in a molar ratio of 1:2.5:0.04:2.5:2.5, and the vanadium source and citric acid are dissolved in deionized water to obtain solution A, and the sodium source, bismuth source, and phosphorus source are dissolved in deionized water to obtain solution B. After mixing solution A and solution B, they are placed in a water bath at 80°C and heated and stirred at a constant temperature for 1 hour to stabilize the color of the solution at blue, and then sodium bicarbonate is added (sodium bicarbonate is 3% of the amount of the added vanadium source), and stirring is continued for 7.5 hours to form a gel, and then dried in a vacuum oven at 120°C for 13 hours, ground into powder, and then placed in a nitrogen atmosphere and sintered at 750°C for 7 hours to obtain porous carbon@bismuth-doped sodium vanadium phosphate material.
[0058] S2. Preparation of B2O3 coating layer: The porous carbon-coated bismuth-doped sodium vanadium phosphate material obtained in step S1 is ball-milled with B2O3 for 2 hours (B2O3 is 0.7wt% of the porous carbon-coated bismuth-doped sodium vanadium phosphate material), then placed in a nitrogen atmosphere, sintered at 850°C for 10 hours, and cooled to room temperature to obtain B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (the bismuth content is 0.51wt%, the porous carbon content is 0.9wt%, and the B2O3 content is 0.65wt%).
[0059] Example 3 Preparation of sodium positive electrode material
[0060] S1. Preparation of porous carbon-coated bismuth-doped sodium vanadium phosphate material: Vanadium pentoxide, sodium carbonate, bismuth nitrate, ammonium dihydrogen phosphate, and citric acid are weighed in a molar ratio of 1:2.2:0.05:2.8:2.8, the vanadium source and citric acid are dissolved in deionized water to obtain solution A, and the sodium source, bismuth source, and phosphorus source are dissolved in deionized water to obtain solution B. Solution A and solution B are mixed and placed in a water bath at 80°C for constant heating and stirring for 1 hour to stabilize the color of the solution at blue, and then sodium bicarbonate is added (sodium bicarbonate is 4% of the amount of the added vanadium source) and stirred for 8 hours until a gel is formed, and then dried in a vacuum oven at 120°C for 14 hours and ground into powder, and then placed in an inert atmosphere and sintered at 800°C for 6 hours to obtain porous carbon@bismuth-doped sodium vanadium phosphate material.
[0061] S2. Preparation of B2O3 coating layer: The porous carbon-coated bismuth-doped sodium vanadium phosphate material obtained in step S1 is ball-milled with B2O3 for 4 hours (B2O3 is 0.9wt% of the porous carbon-coated bismuth-doped sodium vanadium phosphate material), then placed in a nitrogen atmosphere, sintered at 900°C for 8 hours, and cooled to room temperature to obtain B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (the bismuth content is 0.72wt%, the porous carbon content is 0.6wt%, and the B2O3 content is 0.79wt%).
[0062] Example 4
[0063] A sodium positive electrode material was prepared according to the method of Example 1, except that the amount of B2O3 used in step S1 was 0.2wt% of the porous carbon-coated bismuth-doped sodium vanadium phosphate material, and the other conditions were the same as in Example 1, thereby preparing B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (the bismuth content was 0.36wt%, the porous carbon content was 1.4wt%, and the B2O3 content was 0.15wt%).
[0064] Example 5
[0065] A sodium positive electrode material was prepared according to the method of Example 1, except that the amount of B2O3 used in step S1 was 1.5wt% of the porous carbon-coated bismuth-doped sodium vanadium phosphate material, and the other conditions were the same as in Example 1, thereby preparing B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (the bismuth content was 0.31wt%, the porous carbon content was 0.6wt%, and the B2O3 content was 1.42wt%).
[0066] Example 6
[0067] A sodium positive electrode material was prepared according to the method of Example 1, except that the molar ratio of sodium acetate to bismuth nitrate in step S1 was 3:0.01, and the other conditions were the same as in Example 1, thereby preparing B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (bismuth content was 0.17wt%, porous carbon content was 1.3wt%, and B2O3 content was 0.55wt%).
[0068] Example 7
[0069] A sodium positive electrode material was prepared according to the method of Example 1, except that the molar ratio of sodium acetate to bismuth nitrate in step S1 was 3:0.07, and the other conditions were the same as in Example 1, thereby preparing B2O3@porous carbon@bismuth-doped sodium vanadium phosphate sodium positive electrode material (bismuth content was 0.92wt%, porous carbon content was 1.1wt%, and B2O3 content was 0.51wt%).
[0070] Comparative Example 1 Preparation of Reference Sodium Electrode Cathode Material
[0071] Preparation of sodium vanadium phosphate positive electrode material: ammonium metavanadate, sodium acetate, ammonium dihydrogen phosphate, and citric acid are weighed in a molar ratio of 2:3:3:3, the vanadium source and citric acid are dissolved in deionized water to obtain solution A, and the sodium source, bismuth source, and phosphorus source are dissolved in deionized water to obtain solution B. Solution A and solution B are mixed and placed in a water bath at 80°C for constant heating and stirring for 1 hour to stabilize the color of the solution at blue, and stirring is continued for 7 hours to form a gel, and then dried in a vacuum oven at 120°C for 12 hours and ground into powder, and then sintered at 700°C in an air atmosphere for 8 hours to obtain sodium vanadium phosphate material (bismuth content is 0, porous carbon content is 0, and B2O3 content is 0).
[0072] Comparative Example 2 Preparation of Reference Sodium Electrode Cathode Material
[0073] A reference sodium positive electrode material was prepared according to the method of Example 1, except that bismuth nitrate was not added in step S1, and the other conditions were the same as those in Example 1, thereby preparing a reference sodium positive electrode material (B2O3@porous carbon@sodium vanadium phosphate).
[0074] Comparative Example 3 Preparation of Reference Sodium Electrode Cathode Material
[0075] A reference sodium positive electrode material was prepared according to the method of Example 1, except that sodium bicarbonate was not added in step S1 and sintering was carried out in an air atmosphere. The other conditions were the same as those in Example 1, thereby preparing a reference sodium positive electrode material (B2O3@bismuth-doped sodium vanadium phosphate).
[0076] Comparative Example 4 Preparation of Reference Sodium Electrode Cathode Material
[0077] A reference sodium positive electrode material was prepared according to the method of Example 1, except that step S2 was not performed, and the porous carbon-coated bismuth-doped sodium vanadium phosphate material prepared directly according to the method of step S1 was used as the reference sodium positive electrode material (porous carbon@bismuth-doped sodium vanadium phosphate).
[0078] Comparative Example 5 Preparation of Reference Sodium Electrode Cathode Material
[0079] A reference sodium positive electrode material was prepared according to the method of step S1 in Example 1, except that bismuth nitrate was not added and step S2 was not performed, and the other conditions were the same as step S1 in Example 1, thereby preparing a reference sodium positive electrode material (porous carbon@sodium vanadium phosphate).
[0080] Comparative Example 6 Preparation of Reference Sodium Electrode Cathode Material
[0081] A reference sodium positive electrode material was prepared according to the method of step S1 in Example 1, except that sodium bicarbonate was not added in step S1 and sintering was performed in an air atmosphere and step S2 was not performed. The remaining conditions were the same as those in step S1 of Example 1, thereby preparing a reference sodium positive electrode material (bismuth-doped sodium vanadium phosphate).
[0082] Comparative Example 7 Preparation of Reference Sodium Electrode Cathode Material
[0083] The sodium vanadium phosphate material prepared in Comparative Example 1 was ball-milled and mixed with B2O3 for 3 hours, wherein the amount of B2O3 was 0.6wt% of the sodium vanadium phosphate material, and then sintered at 800°C for 12 hours and cooled to room temperature to obtain B2O3@sodium vanadium phosphate material as a reference sodium positive electrode material (B2O3@sodium vanadium phosphate).
[0084] Test Case
[0085] The sodium positive electrode materials prepared in the above examples and comparative examples were assembled into button cells according to the following method and the cycle performance and rate performance were tested. The results are shown in Table 1.
[0086] (1) Button cell assembly: Sodium positive electrode material (96 wt%), CNT (1%), conductive agent (1 wt% SP), binder (2 wt% PVDF) and NMP solution are mixed into positive electrode slurry, which is coated and dried to obtain positive electrode sheets. The positive and negative electrode sheets, separators and electrolytes are assembled into CR2032 button cells.
[0087] (2) Rate performance: At 25°C, charge to 4.0 V at 1C constant current and constant voltage, with a cut-off current of 0.05C, leave for 10 min, then discharge to 2.5 V at 1C constant current, leave for 10 min, and record the discharge capacity at this time;
[0088] Charge to 4.0V at 1C constant current and constant voltage, cut off current 0.05C, leave for 10min, discharge to 2.5V at 5C constant current, leave for 10min, record the discharge capacity at this time;
[0089] Charge to 4.0V at 1C constant current and constant voltage, cut off current 0.05C, leave for 10min, discharge to 2.5V at 10C constant current, leave for 10min, record the discharge capacity at this time;
[0090] The rate performance was calculated by dividing the discharge capacity at 5 C by the discharge capacity at 1 C and by dividing the discharge capacity at 10 C by the discharge capacity at 1 C.
[0091] Cycle performance: The button cell assembled according to the method in (1) was charged to 4.0 V at 1 C constant current and constant voltage at 25°C, with a cut-off current of 0.05 C, left for 30 min, and then discharged to 2.5 V at 1 C constant current, thus completing a charge and discharge cycle. After repeating 600 cycles, the discharge capacity at this time was recorded, and the capacity retention rate after 600 cycles was calculated.
[0092] Table 1
[0093]
[0094] It can be seen from the results of Table 1 that, compared with Comparative Examples 1 to 7, the sodium positive electrode materials of B2O3@porous carbon@bismuth-doped sodium vanadium phosphate prepared in Examples 1 to 7 of the present invention have better cycle capacity performance, and better rate performance at different current densities and even at a high current density of 10C. From the results of Example 1 and Comparative Example 1, it can be seen that compared with the sodium vanadium phosphate material without any modification, the B2O3@porous carbon@bismuth-doped sodium vanadium phosphate positive electrode material prepared in Example 1 has better cycle capacity retention and rate performance. From the results of Example 1 and Comparative Examples 2 to 7, it can be seen that if any one or two of bismuth doping, porous carbon coating, and B2O3 coating are missing, the cycle capacity retention and rate performance will be significantly reduced.
[0095] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A sodium positive electrode material, characterized in that: The sodium positive electrode material comprises a bismuth-doped sodium vanadium phosphate core and a first coating layer and a second coating layer sequentially coated on the surface of the bismuth-doped sodium vanadium phosphate core from the inside to the outside; the first coating layer is porous carbon, and the second coating layer is B2O3.
2. The sodium positive electrode material according to claim 1, characterized in that The bismuth content in the bismuth-doped sodium vanadium phosphate core is 0.3-0.8wt%; preferably, the porous carbon content in the sodium positive electrode material is 0.5-1.5wt%; preferably, the B2O3 content in the sodium positive electrode material is 0.5-1wt%.
3. A method for preparing a sodium positive electrode material, characterized in that: The preparation method comprises the following steps: S1. After a sodium source, a vanadium source, a bismuth source, a phosphorus source, citric acid and water are subjected to a first mixing treatment, the obtained first intermediate product is subjected to a pore-forming treatment in the presence of an activator, and the obtained second intermediate product is subjected to a first calcination treatment to obtain a porous carbon @ bismuth-doped sodium vanadium phosphate material; S2. After the porous carbon@bismuth-doped sodium vanadium phosphate material is subjected to a second mixing treatment with B2O3, the obtained third intermediate product is subjected to a second calcination treatment to obtain a sodium positive electrode material.
4. The method for preparing a sodium positive electrode material according to claim 3, characterized in that: The molar ratio of the vanadium source to the sodium source, the bismuth source, the phosphorus source and the citric acid is 1:(1-3):(0.015-0.05):(1.5-3):(1.5-3); Preferably, the molar ratio of the activator to the vanadium source is (0.02-0.05):1; Preferably, the amount of B2O3 used is 0.5-1 wt% of the porous carbon@bismuth-doped sodium vanadium phosphate material.
5. The method for preparing a sodium positive electrode material according to claim 3, characterized in that: The sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate; Preferably, the vanadium source is selected from ammonium metavanadate and / or vanadium pentoxide; Preferably, the bismuth source is selected from bismuth nitrate and / or bismuth acetate; Preferably, the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium phosphate; Preferably, the activator is selected from at least one of sodium bicarbonate, potassium bicarbonate, potassium hydroxide and sodium hydroxide.
6. The method for preparing a sodium positive electrode material according to claim 3, characterized in that: The conditions of the first mixing treatment include: a temperature of 70 to 90° C. and a time of 1 to 3 hours; Preferably, the conditions of the pore-forming treatment include: a temperature of 70 to 90° C. and a time of 7 to 8 hours; Preferably, the second mixing process is a ball milling process; Preferably, the second mixing treatment is performed for 2 to 4 hours.
7. The method for preparing a sodium positive electrode material according to claim 3, characterized in that: The conditions of the first calcination treatment include: a temperature of 700 to 800° C., a time of 6 to 8 hours, and an inert gas atmosphere; Preferably, the conditions of the second calcination treatment include: a temperature of 800 to 900° C. and a time of 8 to 15 hours.
8. A sodium positive electrode material prepared by the method according to any one of claims 3 to 7.
9. A sodium battery positive electrode sheet, characterized in that: The sodium battery positive electrode sheet comprises the sodium battery positive electrode material according to claim 1, 2 or 8.
10. A sodium battery, characterized in that: The sodium battery comprises the sodium positive electrode material according to claim 1, 2 or 8.